A Rare Case of Urinary Tract Fungal Ball Leading to Fungemia and Bilateral Chorioretinitis. (28th September 2020) - Ferari, Christopher; Crigger, Chad; Morley, Chad
Abstract : Background . Fungemia due to obstructive urinary tract fungal ball is exceedingly rare. These patients often have multiple predisposing conditions, including diabetes or antimicrobial exposure. While candiduria can be relatively common in this population, urinary tract fungal balls are a rare entity. Hospitalists should be aware of this rare complication in patients presenting with funguria. Case Presentation . We present a case of a 44-year-old male with type II diabetes, chronic hepatitis C secondary to injection drug use, and chronic kidney disease who developed a urinary tract fungal ball leading to fungemia and subsequent bilateral chorioretinitis, additionally complicated by emphysematous cystitis and pyelonephritis. Additional invasive treatment options beyond typical antifungals are often required in the case of urinary tract fungal ball, and in this case, bilateral nephrostomy tubes and micafungin were employed. Hospital course was complicated by C. tropicalis fungemia with subsequent bilateral fungal chorioretinitis on dilated fundus exam. This was effectively treated with cyclogyl and prednisolone drops along with bilateral voriconazole injections. Follow-up imaging and cultures showed resolution of fungemia, urinary tract masses, and chorioretinal infiltrates; however, recurrent polymicrobial UTIs continue to be an issue for this patient. Conclusions . Special multidisciplinary management is required in the treatment of urinary tract fungal balls with subsequent fungemia, including nephrostomy tubes, antifungal irrigation, ureterorenoscopy, and more powerful antifungals such as amphotericin B and 5-flucytosine. This management draws from a myriad of specialties, including urology, infectious disease, and interventional radiology. Additionally, the literature has demonstrated that only approximately half of patients with fungemia receive an ophthalmologic evaluation. Ophthalmologic and urologic cooperation is essential in the case of obstructive uropathy leading to fungemia as the obstructive uropathy must be relieved and these patients should receive a dilated fundus exam.